At the Interface of Medicine and Dance - Long, Madison D. (My University, 2019)
This paper will combine the arts and sciences in such a manner as to address the overwhelming prevalence of suicide in today’s society. An introduction will be given first to present the reader with the barriers of collaboration between the arts and sciences as well as to describe how the author chose to bring about an interdisciplinary perspective through the use of this particular topic of suicide. Next, the performance of the dance component of this Honors Project entitled In Loving Memory will be explained from the importance of the speech to the significance of the story that is told throughout the piece. After which, the paper will shift towards the pre-medical aspect of the project, addressing first how physicians can be more aware of the signs contributing to suicide within their patients. Then, the topic of suicide as a public health issue will be further examined. To finish it all up, a quick overview will be given, hitting the highpoints of this Honors Project and the issues that suicide presents to today’s physicians and society as a whole.